The reality of Imam Al-Mahdi in the light of Islamic Shariah - WAQAR, Dil Aqa; Azizi, Shirzad (Journal of Islamic Sciences, 2023)
This study attempts at clarifying the ambiguity that exist among the people (particularly among the Sunnis and the Shiites) regarding who the Imam Mahdi is? When is he going to emerge? Is it real or is it an imaginary myth that has no truth? Hence, the key objective of this study is to investigate and present the reality of the Mahdi in the light of Islamic Shariah, and this is just for the importance that this subject matter holds among Muslims. The study has adopted an analytical and comparative research method to achieve the objectives. The result of the study highlights that Sunnis believe that the Mahdi is Muhammad bin Abdullah, a descendent of the Prophet from the line of (Al-Hassan bin Ali “RA”), that will emerge at the end time, invite people to the right path, and order with justice. However, the Imami Shiites believe in the appearance of the absent Mahdi, who is the last imam of their imams, just as they believe in the chain of the Imamate, starting from Ali (kw), then Hassan and Hussein, to Muhammad ibn al-Hassan, the absent Mahdi, from the sons of Imam Hussein (ra). However, most Shiites say that the Mahdi does not exist now and that he will emerge at the end of time. The author of the study recommends the people, particularly, Muslims not to take extremist position in sub-topics of Islam and only focus on principle issues of the Islam, forgive each other in sub-issues, and conduct research with sincerity and good intentions.